Lactulose as a prebiotic improved the intestinal health and metabolism of geese - Wang, Xiaoxue; Ye, Pengfei; Zhu, Jie; Zhu, Xueqi; He, Xiaorong; Meng, Yu; Cao, Shiyan; Zhao, Lei (Frontiers in Veterinary Science, 2025)
Lactulose is highly valued for its unique role in promoting the growth of intestinal probiotics. The objective of this research was to investigate how varying levels of dietary protein combined with lactulose supplementation influence the intestinal health of geese, utilizing intestinal metabolomics as the analytical basis. A total of 210 one-day-old Yangzhou geese were randomly assigned to three dietary treatments, with each group consisting of 7 replicates of 10 birds each. The diet of the control group (CP) contained 18.18% crude protein, the high-protein group (HP) was provided a diet formulated to 21.12% crude protein, and the lactulose-supplemented group (LS) received the high-protein diet (21.12%) with an additional 0.30% lactulose inclusion. The results showed that compared with the HP group, lactulose increased the average daily weight gain of geese (p < 0.05), reduced the feed conversion rate (p > 0.05), and decreased the level of uric acid in serum (p < 0.05). At the same time, lactulose improved the morphological structure of the ileum and increased the intestinal villus height (VH) (p < 0.01) and villus height/crypt depth ratio (VH/CD) (p < 0.05). Compared with HP, the total number of aerobic bacteria, Escherichia coli and Salmonella in cecum decreased by 2.70, 9.28 and 12.26%, respectively. Non-targeted metabolomics analysis showed that lactulose regulated intestinal barrier structure and intestinal flora through glycerophospholipid metabolism and fatty acid metabolism, which further improved the intestinal health of geese.